Mixed Reality and Three-Dimensional Computer Graphics (IntechOpen, 2020)
Mixed reality is an area of computer research that deals with the combination of real-world and computer-generated data, where computer-generated objects are visually mixed into the real environment and vice versa in real time. It is the newest virtual reality technology. It usually uses 3D computer graphics technologies for visual presentation of the virtual world. The mixed reality can be created using the following technologies: augmented reality and augmented virtuality. Mixed and virtual reality, their applications, 3D computer graphics and related technologies in their actual stage are the content of this book. 3D-modeling in virtual reality, a stereoscopy, and 3D solids reconstruction are presented in the first part. The second part contains examples of the applications of these technologies, in industrial, medical, and educational areas.